Geographical contexts of entrepreneurship: Spaces, places and entrepreneurial agency - Erik Stam; Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2020)
This chapter focuses on contexts of entrepreneurship, in particular geographical contexts, and entrepreneurial agency. The twin concepts space and place are key in understanding geographical contexts for entrepreneurship, not least because place does not exist without physical space. Important research in this regard has touched upon the role of gendered places and spaces for entrepreneurship, social places such as families, households and neighbourhoods and explored new spaces for entrepreneurship such as makerspaces. We combine these spaces and places in a model of entrepreneurial ecosystems that allows us to focus simultaneously on the geographical contexts for entrepreneurship and the agency of entrepreneurs within those. The chapter ends with a future research agenda on geographical contexts for entrepreneurship. – – Der Artikel konzentriert sich auf die Kontexte des Unternehmertums - insbesondere jedoch auf den Zusammenhang zwischen geographischen Kontexten und unternehmerischem Handeln. Dabei sind die Begriffe "Raum" und "Ort" für das Verständnis geografischer Kontexte im Zusammenhang mit Unternehmertum von zentraler Bedeutung - nicht zuletzt, weil es keinen Ort ohne physischen Raum gibt. Wichtige Forschungsarbeiten in diesem Zusammenhang haben sich mit der Rolle geschlechtsspezifischer Orte und Räume für das Unternehmertum, sozialen Orten wie Familien, Haushalten und Nachbarschaften befasst und neue Räume für das Unternehmertum wie Makerspaces erforscht. Wir kombinieren diese Räume und Orte in einem Modell unternehmerischer Ökosysteme, so dass wir uns gleichzeitig auf die geografischen Kontexte für das Unternehmertum und das unternehmerische Handeln innerhalb dieser konzentrieren können.
Keywords: 330